Ferrihydrite Reduction by Photosynthetic Synechocystis sp. PCC 6803 and Its Correlation With Electricity Generation - Tanaka, Kenya; Shimakawa, Ginga; Kusama, Shoko; Harada, Takashi; Kato, Souichiro; Nakanishi, Shuji (Frontiers in Microbiology, 2021)
Microbial extracellular electron transfer (EET) to solid-state electron acceptors such as anodes and metal oxides, which was originally identified in dissimilatory metal-reducing bacteria, is a key process in microbial electricity generation and the biogeochemical cycling of metals. Although it is now known that photosynthetic microorganisms can also generate (photo)currents via EET, which has attracted much interest in the field of biophotovoltaics, little is known about the reduction of metal (hydr)oxides via photosynthetic microbial EET. The present work quantitatively assessed the reduction of ferrihydrite in conjunction with the EET of the photosynthetic microbe Synechocystis sp. PCC 6803. Microbial reduction of ferrihydrite was found to be initiated in response to light but proceeded at higher rates when exogenous glucose was added, even under dark conditions. These results indicate that current generation from Synechocystis cells does not always need light irradiation. The qualitative trends exhibited by the ferrihydrite reduction rates under various conditions showed significant correlation with those of the microbial currents. Notably, the maximum concentration of Fe(II) generated by the cyanobacterial cells under dark conditions in the presence of glucose was comparable to the levels observed in the photic layers of Fe-rich microbial mats.